Conscientious Objection in Healthcare Provision: A New Dimension - West-Oram, Peter; Buyx, Alena (Bioethics, 2016)
The right to conscientious objection in the provision of healthcare is the subject of a lengthy, heated and controversial debate. Recently, a new dimension was added to this debate by the US Supreme Court's decision in Burwell vs. Hobby Lobby et al. which effectively granted rights to freedom of conscience to private, for-profit corporations. In light of this paradigm shift, we examine one of the most contentious points within this debate, the impact of granting conscience exemptions to healthcare providers on the ability of women to enjoy their rights to reproductive autonomy. We argue that the exemptions demanded by objecting healthcare providers cannot be justified on the liberal, pluralist grounds on which they are based, and impose unjustifiable costs on both individual persons, and society as a whole. In doing so, we draw attention to a worrying trend in healthcare policy in Europe and the United States to undermine women's rights to reproductive autonomy by prioritizing the rights of ideologically motivated service providers to an unjustifiably broad form of freedom of conscience.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Abortion; Affordable Care Act; Conscientious objection; Contraception; Hobby Lobby; Pluralism; Reproductive autonomy